2007
DOI: 10.1021/nl070194h
|View full text |Cite
|
Sign up to set email alerts
|

Power Generation by Pressure-Driven Transport of Ions in Nanofluidic Channels

Abstract: We report on the efficiency of electrical power generation in individual rectangular nanochannels by means of streaming currents, the pressure-driven transport of counterions in the electrical double layer. Our experimental study as a function of channel height and salt concentration reveals that the highest efficiency occurs when double layers overlap, which corresponds to nanoscale fluidic channels filled with aqueous solutions of low ionic strength. The highest efficiency of approximately 3% was found for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
409
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 519 publications
(454 citation statements)
references
References 17 publications
29
409
1
6
Order By: Relevance
“…[2][3][4] Others have concentrated on the electrical properties of single well-defined channels. [5][6][7][8][9][10] Similarly, in a recent paper, we demonstrated intrinsic electrokinetic molecular hydrogen production by flowing pure water through metal microchannels.…”
Section: Introductionsupporting
confidence: 59%
“…[2][3][4] Others have concentrated on the electrical properties of single well-defined channels. [5][6][7][8][9][10] Similarly, in a recent paper, we demonstrated intrinsic electrokinetic molecular hydrogen production by flowing pure water through metal microchannels.…”
Section: Introductionsupporting
confidence: 59%
“…A nanosystem is an integration of nanodevices, functional components, and a power source. Energy harvesting from the environment for powering a nanosystem is vitally important for its independent, wireless, and sustainable operation [495][496][497]555]. A piezoelectric nanogenerator is a promising approach for this application [22].…”
Section: Self-powered Nanosystemsmentioning
confidence: 99%
“…Of particular interest is the intricate interplay among surface chemistry, electrokinetics, and fluid dynamics spanning over molecular and continuum macroscopic length scales [4,5]. It has been demonstrated that the electrokinetic properties at this scale have enabled a range of innovations including those for chemical sensing and bioanalytics [6][7][8][9][10][11][12], energy harvesting systems, [13][14][15][16][17][18], and nanofluidic ion transport [19][20][21][22][23][24][25][26], including enrichment, depletion, and rectification effects [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%